PENGARUH KEPUASAN KERJA DAN LINGKUNGAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR KARYAWAN PT. PERKEBUNAN NUSANTARA XIV - Andi Hendro; Muh Ilham Alimuddin (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
This study aims to determine the effect of work and work environment on organizational citizenship behavior at PT. Perkebunan Nusantara XIV. Sources of data in this study are primary data and secondary data as well as data collection methods with interviews and questionnaires. The data analysis method used was simple multiple linear regression analysis. The results showed that work goals and work environment had a positive and significant effect on organizational citizenship behavior at PT. Perkebunan Nusantara XIV.